2018
DOI: 10.18632/oncotarget.25758
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-mediated autophagy inhibits DNA damage-induced death of leukemia cells independent of p53

Abstract: Autophagy is important in regulating the balance between cell death and survival, with the tumor suppressor p53 as one of the key components in this interplay. We have previously utilized an in vitro model of the most common form of childhood cancer, B cell precursor acute lymphoblastic leukemia (BCP-ALL), to show that activation of the cAMP signaling pathway inhibits p53-mediated apoptosis in response to DNA damage in both cell lines and primary leukemic cells. The present study reveals that cAMP-mediated sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…Overexpression of P53 has been proved to be significantly related to the initiation of HP-HPV transformation infection. 25,26 Ki-67 is a definite marker of nuclear proliferation at present. Its half-life is short.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of P53 has been proved to be significantly related to the initiation of HP-HPV transformation infection. 25,26 Ki-67 is a definite marker of nuclear proliferation at present. Its half-life is short.…”
Section: Discussionmentioning
confidence: 99%
“…It is also a disorder of the entering S phase from G1 phase, thereby inhibiting cell proliferation. Overexpression of p53 has been proved to be significantly related to the initiation of HP-HPV transformation infection [25,26] . Ki67 is a definite marker of nuclear proliferation at present.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mechanisms underlying the reciprocal functional interaction of autophagy-p53 are not yet fully understood. Although p53 induces the transcription of autophagy-related genes, such as AMPK β1/β2 , DRAM and DAPK-1 [ 28 , 29 ], a previous study suggested that lowering the levels of p53 may facilitate autophagy [ 30 ]. In addition, it has been reported that autophagy suppresses p53 expression [ 31 ].…”
Section: Discussionmentioning
confidence: 99%